Domestic Tourist Interest in Lake Toba Tourism Area Destinations - Beby Karina F.S; Anitha Paulina Tinambunan; Kornel Munthe; Donalson Silalahi; Miska Irani Tarigan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The tourism area around Lake Toba is part of the Indonesian government's super-priority destination program. The goal of this study was to figure out where each destination was on the respondent's mind map. Purposive sampling was used to select 103 participants for this investigation. The results of data processing with SPSS display a three-dimensional perceptual map, with dimension 1 representing the destination image in the Lake Toba tourist area, dimension 2 representing the destination brand experience (Brand experience destination), and dimension 3 representing the attraction in regional Lake Toba tours. Then, based on the Euclidean distance, a destination group was constructed, which was viewed as having a similarity level. Taman Iman Sitinjo, Lae Pandaroh Waterfall, Tuktuk, Hot Springs, and Sipiso-Piso Waterfall have created a single group that is in direct competition with one another. Balige, Sisingamangaraja Palace, and the Salib Kasih are the other groups. Parapat and Tomok, meanwhile, created their own groups. RSQ = 0.76 and Stress = 0.17 are the outcomes.